ANALISIS EFISIENSI PENGGUNAAN TEMPAT TIDUR PADA UNIT PELAYANAN NICU BERDASARKAN INDIKATOR PELAYANAN KESEHATAN DI RSUD DR. DRADJAT PRAWIRANEGARA KAB. SERANG - Cahya, Heru Indra; Tho, Ita La; Muhtaruddin, Erwin (Ensiklopedia of Journal, 2024)
Abstract: Hospitals are a health care institution that organizes plenary health services that provide inpatient services, outpatient and emergency depth. In providing health services to the community, hospitals must pay attention to the quality of health services to the community. Quality health services are one of the benchmarks of satisfaction that has for the desire of patients to return to institutions that provide effective health services, including inpatient services. Inpatient services will be able to influence the level of efficiency in the hospital. The level of efficiency of inpatient services is not enough only with raw data or data from the daily census of hospitalization, but must be processed first into the indicators of hospitalization (Bed occupancy ratio), Alos (Average Length of Stay), TOI (turn over interval) and BTO (Bed Turn Over). This study aims to analyze the efficiency of the use of beds in the NICU service unit based on health care indicators in RSUD Dr. Dradjat Prawiranegara Kab. Attack. This type of research is quantitative research with a descriptive approach to data collection using observation, interviews and documentation studies. The type of research used in this study is descriptive quantitative with a retrospective approach with the survey method using a checklist sheet. Data sample data recapitulation of hospitalization daily census in the NICU service unit 2022 and 2023 periods. The results showed that the efficiency of the use of beds in the NICU service unit at RSUD DR. Dradjat Prawiranegara Kab. Serang based on the Bed Occupancy rate of 86% in the period 2022 and amounting to 102% in 2023; Based on the value of ALOS (Average Length of Stay), 14 days in the period 2022 and 13 days in the period of 2023; Based on the TOI value (turn over interval), which in the period 2022 exceeded the ideal value of 4 days and had not yet reached an ideal value in 2023 by -1 days; Based on the value of BTO (Bed Turn Over), which was 1222 / year by 2023 in 2023 9 times / year. So for the drill value, Alos, Toi and BTO on the NICU service unit at RSUD Dr. Dradjat Prawiranegara Kab. Serang in the period 2022 and 2023, which is inefficient. Too high use of beds, so it needs to be a hospital development or addition of beds, especially the NICU service unit in RSUD Dr. Dradjat Prawiranegara Kab. Serang period 2022 and 2023Keywords: efficiency, bed use, health care indicators